N, S co-doped carbon with embedment of FeNi alloy as bifunctional oxygen electrocatalysts for rechargeable Zinc-air batteries. (15th January 2023) - Wu, Run; Wang, Xixi; Ge, Lei; Zheng, Zehao; Zhu, Yijun; Zhou, Chuan; Yuan, Jinglin; Zhu, Shiliang; Gu, Yuxing; Zhou, Wei; Shao, Zongping
Abstract: Zinc-air batteries (ZABs) have sparked great interest, but their wide-ranging applications are limited by sluggish cathode reactions (ORR and OER). In this work, a multifunctional 3D catalyst (FeNi alloy/porous carbon) was easily fabricated by introducing Fe 3+ and Ni 2+ to modulate in-situ vapor phase grown carbon nanotubes. The as-prepared catalyst FNSNC73-800 displays abundant mesoporous, massive structural defects, and multiple active sites, which greatly facilitate the transport of oxygen species and charge transfer during the reaction. Due to the excellent ORR and OER performance, FNSNC73-800 shows a narrow voltage gap (Δ E ) of 0.76 V, which is superior to recent reports. Notably, the secondary zinc-air battery with this catalyst displays a high-peak power density (210 mW cm −2 ), while maintaining an ultra-low potential gap (0.74 V) after a long-term charge-discharge cycle of 200 h. This effort presents a facile strategy for designing economical and efficient 3D catalysts for zinc-air batteries and more energy devices. Graphical abstract: 3D porous FeNi alloy/porous carbon as air cathode catalyst displays outstanding ORR and OER activities in Zinc-air batteries. Image 1